2017
DOI: 10.1364/oe.25.018897
|View full text |Cite
|
Sign up to set email alerts
|

140 W peak power laser system tunable in the LWIR

Abstract: We present a high peak power rapidly tunable laser system in the long-wave infrared comprising an external-cavity quantum cascade laser (EC-QCL) broadly tunable from 8 to 10 µm and an optical parametric amplifier (OPA) based on quasi phase-matching in orientation-patterned gallium arsenide (OP-GaAs) of fixed grating period. The nonlinear crystal is pumped by a pulsed fiber laser system to achieve efficient amplification in the OPA. Quasi phase-matching remains satisfied when the EC-QCL wavelength is swept from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In ref [1], we implemented a parametric oscillator, pumped by a 2 µm microlaser, in which wavelength tunability was achieved by temperature tuning of the crystal indices of refraction. An attractive alternative to address a similar wavelength range with a significantly faster tuning speed is to change the pump wavelength rather than the crystal temperature [2]. In this context, to control the spectral output of the optical parametric oscillator (OPO), which is based on Vernier spectral filtering in doubly resonant cavities [1], we also need a single longitudinal mode (SLM) pump laser.…”
Section: Contextmentioning
confidence: 99%
“…In ref [1], we implemented a parametric oscillator, pumped by a 2 µm microlaser, in which wavelength tunability was achieved by temperature tuning of the crystal indices of refraction. An attractive alternative to address a similar wavelength range with a significantly faster tuning speed is to change the pump wavelength rather than the crystal temperature [2]. In this context, to control the spectral output of the optical parametric oscillator (OPO), which is based on Vernier spectral filtering in doubly resonant cavities [1], we also need a single longitudinal mode (SLM) pump laser.…”
Section: Contextmentioning
confidence: 99%
“…The nonlinear coefficient of OP-GaAs is very large (d 14 = 94 pm/V), and it was used to achieve an average pulse energy of 0.18 mJ at 8.5 µm [4] and 16.2 µJ at 10.6 µm [5], corresponding to the repetition frequencies of 2 and 50 kHz, respectively. AgGaSe 2 has a low damage threshold (18 MW/cm 2 ), which limits its ability to obtain a large-energy long-wave infrared laser.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, large-scale wavelength tunability of the NesCOPO was previously achieved by temperature tuning of the index of refraction of the nonlinear crystal of the OPO, which is too slow for practical differential absorption measurements. It is well known that OPO wavelength tuning could be done faster by tuning the pump wavelength rather than the crystal temperature [4]. Simple calculations showed that tuning of the 2 µm pump over 20 nm is enough to address a similar tuning range as in [1], i.e.…”
Section: Introductionmentioning
confidence: 99%